Power Series Matrices - Izmirli, Ilhan M. (Transactions on Engineering and Computing Sciences, 2024)
In this paper, we propose an algorithm that can be used to construct the elements of any power series matrix generated by any polynomial . As such, this algorithm is a generalization of the specific algorithms that give us the Pascal and the Fibonacci matrices. We will first start with the special cases of Pascal and Fibonacci matrices. The general case of power series matrices will be analyzed in Section2. We will conclude our paper by giving the algorithm in section 3.